Kombucha and Jamu Kombucha and Jamu Herbal Drinks for Body Health, Between Old and Young Taste - Gintu, Agung Rimayanto; Adelce Rumpeniak; Rosiana E, Rayanti; Dhanang Puspita (Fakultas Teknik Universitas Wahid Hasyim, 2025)
Kombucha and Jamu were the herbal beverages famous nowadays. Those two beverages famous because claimed that it has health benefits when consumed. The trend about Herbal beverages consumptions were appearance anymore because the reports of “side effect” of synthetic chemicals used in medic. The herbal fitochemicals believed has minimum side effect and low toxicity cause the consumption became trend of “health Lifestyle”. In this research produce the Kombucha and Jamu from the herbals and fruits. Phytochemical characterization of the fresh organic and it products (Jamu and Kombucha) showed that those products contains phytochemicals recommended for body heatlh. But from the organoleptic test, the Kombuca preffered by the Teens than Jamu. The reason were because Jamu appearance, taste and aroma more similar too the spices than medicine. Based on this results then recommended to produce the jamu which closer too the taste of the teens.